Colonoscopic polypectomy: Analysis of 429 cases - Sengul, Serkan; Kubat, Mehmet (Annals of Medical Research, 2022)
Aim: It is well known that most colorectal cancers develop from colon polyps. Therefore, removing polyps found during colonoscopy, regardless of their size and characteristics, is critical because of the risk of developing colorectal cancer. This study aimed to evaluate the outcomes of colonoscopic polypectomy performed in our clinic.Materials and Methods: The data of patients who underwent colonoscopy for various reasons between January 2018 and December 2020 and who had polypectomy performed during the procedure were evaluated retrospectively. These patients were divided into two groups, single polypectomy, and multiple polypectomy cases.Results: Single polyp was detected in 72% (n=309) of the 429 patients included in the study, whereas multiple polyps were detected in 28% (n=120). Of these patients, 62.9% (n=270) were male and 37.1% (n= 159) were female. The median age of patients with a single polyp (61.0) was lower than that of patients with multiple polyps (65.0) (p= 0.014). In patients with a single polyp, the most common localization was rectum (32.4%), and the most common histopathological subtype was tubular adenoma (50.8%). In patients who underwent multiple polypectomies, the most common localization was a sigmoid colon (25.5%), while the most common histopathological subtype was again tubular adenoma (48.1%). There was no statistically significant difference between the two groups in the severity of dysplasia (p = 0.838). A significant difference was found between polyp diameter and dysplasia severity in adenomatous polyps in both groups (p
Keywords: Colon polyp; Polypectomy; Adenoma